Not a melting pot: Plant species aggregate in their non‐native range. Issue 3 (17th December 2019) - Stotz, Gisela C.; Cahill, James F.; Bennett, Jonathan A.; Carlyle, Cameron N.; Bork, Edward W.; Askarizadeh, Diana; Bartha, Sandor; Beierkuhnlein, Carl; Boldgiv, Bazartseren; Brown, Leslie; Cabido, Marcelo; Campetella, Giandiego; et al.
Abstract: Aim: Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location: Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period: 2012–2016. Major taxa studied: Plants. Methods: We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results: We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions: The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.